Experience with a synthetic bilayer Biodegradable Temporising Matrix in significant burn injury - John E. Greenwood; Bradley J. Schmitt; Marcus J.D. Wagstaff (Elsevier, 2018)
The NovoSorb™ Biodegradable Temporising Matrix (BTM) has been developed and evaluated over the past 12 years, with publications documenting each step. The final step in our evaluation was a pilot human study of the efficacy of BTM in significant (20-50% TBSA full-thickness) burns. Following immediate (or very early) burn excision, BTM implantation was followed by its monitored integration. The timing of delamination and definitive grafting over the integrated polyurethane foam matrix was determined by the subject's physiological status and the availability of split-skin autograft donor site but was typically around four weeks after the burn debridement. Donor site shortage forced serial grafting in some, which required the BTM to remain laminated for up to 7 weeks without ill effect (spontaneous delamination, granulation tissue formation and wound contraction). The five subjects survived. Of 122% TBSA covered by BTM over the 5 subjects, <7% TBSA was removed for failure to adhere/integrate. Issues such as haematoma required removal and replacement of 9% TBSA with fresh BTM, with complete subsequent integration. The scar results at 12 months using POSAS and MAPS scar scales were very good, both subjectively and objectively, considering the size and depth of the initial injuries. The culmination of this work has been the introduction of this novel material into our clinical practice. Keywords: NovoSorb, Biodegradable Temporising Matrix, BTM, Polyurethane, Pilot burn study